A practical overview of the use of amyloid-PET Centiloid values in clinical trials and research - Leonardo Iaccarino; Samantha C. Burnham; Ilke Tunali; Jian Wang; Michael Navitsky; Anupa K. Arora; Michael J. Pontecorvo (NeuroImage: Clinical)
The density of brain amyloid-beta neuritic plaque accumulation, a marker of Alzheimer’s disease (AD), can be visualized and quantified using amyloid-positron emission tomography (PET). Amyloid-PET data can be obtained using different tracers and methodologies; therefore, comparison across studies can be difficult. The introduction of Centiloids in 2015 allowed for the transformation of amyloid-PET quantitative data to a common scale, enhancing comparability across studies and potentially enabling pooled analysis. Since then, Centiloid values have been used increasingly in research and clinical trials for multiple purposes, being tested and validated with a variety of clinical, biomarker and pathological standards of truth. In clinical trials, Centiloid values have been used for patient selection, to confirm the presence of AD pathology, as well as for treatment monitoring, especially in trials of disease-modifying treatments such as amyloid-targeting therapies. Building on their widespread adoption, Centiloid values are increasingly being integrated into commercially available software solutions for quantifying amyloid-PET, paving the way for real-world applications at the community level. This article addresses frequently asked questions about Centiloid definition, implementation, interpretation, and caveats, and also summarizes the available literature on published thresholds, ultimately supporting wider access and informed use of Centiloid values in Alzheimer’s disease research.